Comparative Analysis of the Sustainability of the Social Security Systems in Central Europe - Jakab, Nóra (Sustainability Of The Social Security System: Demographic Challenges and Answers in Central Europe, 2023)
This chapter presents a comparative analysis of the country chapters along the following themes: social security and social protection, the dogmatic issues of social law. This is followed by an analysis of the constitutional arrangements, since, in addition to the arguments for and against the inclusion of social rights in the constitution, it is a question of a choice of values: whether to accept the ‘message’ of social rights, namely that the individual, the citizen, (also) has duties towards the community, the state. The starting point for the preparation of this book is an examination of compliance with the relevant articles of the (Revised) European Social Charter. This document is the most prominent of all Central European countries in this respect. The subsections on sustainability and current regulatory issues have made it possible to present the information gathered in three separate subsections: good practices, sustainability issues and country-specific regulations. KEYWORDS: social security and social protection, dogmatic of social law, level of the protection in the constitution, sustainability, best practices